2022
DOI: 10.1002/ajhb.23748
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in the waist, hips circumferences and selected associated indicators, among preschool children from Kraków (Poland), between 1983 and 2018

Abstract: Objectives Waist circumference and derived indicators are great for measuring the risk of abdominal obesity. The main aim of the study was to assess the changes in the waist, hips circumferences and selected associated indicators, among preschool children (3–7 years of age) from Kraków, Poland, between 1983, 2008 and 2018. Methods The research was conducted in randomly selected kindergarten in Krakow (Poland). The 1983 cohort consisted of 1414 children and the 2008 and 2018 series included 1050 preschoolers ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Importantly, it has also been suggested in previous research, that waist circumference is a better predictor of the health consequences of fat accumulation in children compared to the Body Mass Index (BMI) (McCarthy et al, 2003). That is also in line with the results of a previous study carried out on the Polish pediatric population—also there it was noted that WHR is preferable to body mass index in assessing the risk associated with excess adiposity in the examined population (Kryst et al, 2022, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, it has also been suggested in previous research, that waist circumference is a better predictor of the health consequences of fat accumulation in children compared to the Body Mass Index (BMI) (McCarthy et al, 2003). That is also in line with the results of a previous study carried out on the Polish pediatric population—also there it was noted that WHR is preferable to body mass index in assessing the risk associated with excess adiposity in the examined population (Kryst et al, 2022, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the waist and hips circumferences have been noted to be significant predictors of intra-abdominal adiposity [ 10 , 14 , 15 ]. It should be stressed that in a recent study carried out among Polish preschoolers, it was also observed that WHR was preferable to Body Mass Index in assessing the risk associated with excess adiposity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of older girls (8–15 years old), the prevalence of overweight and high body fat increased slightly. However, the opposite trend was observed in boys (Kryst et al, 2022a).…”
Section: Discussionmentioning
confidence: 93%
“…Also, the trends in adiposity were mostly negative (Żegleń et al, 2020). Nevertheless, is worth noting that between the two most contemporary cohorts, despite the lower amount of adipose tissue in the youngest children and a smaller waist circumference, there was a tendency towards increased accumulation of abdominal fat tissue (Żegleń et al, 2022, Kryst et al, 2022a, 2022b). In the case of older girls (8–15 years old), the prevalence of overweight and high body fat increased slightly.…”
Section: Discussionmentioning
confidence: 99%